The Role of Mean Arterial Pressure (MAP) Roll Over Test (ROT) and Body Mass Index (BMI) in Preeclampsia Screening in Indonesia - Dwi Putri Rahayu Tampubolon (R.K. Sharma, Institute of Medico-Legal Publications, 2020)
Objective: To evaluate the role of MAP, ROT, and BMI in preeclampsia screening in low resources setting. Method and Material: This is a retrospective study conducted on 1011 pregnant women who had an antenatal care at Public Health Center in Indonesia. Data taken from public health medical report. The sample groups were 45 preeclampsia patients who have had complete screening of MAP, ROT and BMI. The control groups were normal pregnant women who attained same inclusion criteria. Results: The pre eclampsia group had positif MAP and obesity result respectively 95.6% and 40% of patients, but in control group only had 40% and 11.1% of patient have positive MAP and obesity respectively. Statistical test illustrates a significant association between MAP and BMI screening with the incidence of preeclampsia (p 0.0001, OR = 32.250 and p 0.002, OR = 5.333).Whereas positive ROT showed in 40% PE groups and 57.8% control group. There is no association between ROT screening and the incidence of preeclampsia (p 0.092). Conclusion: MAP and BMI can be used as baseline screening tools of preeclampsia in low resources setting. But ROT is not associated with the incidence of preeclampsia.